Análise da alimentação de Acestrorhynchus pantaneiro (Characiformes: acestrorhynchidae) em Três Rios do Rio Grande do Sul - Zanini, Lucéle Gonçalves (2012)
To understand the behavior of a species under the reproduction aspects, growth, birth rate, mortality and migration is indispensable the knowledge of his alimentary behavior, still more if treating of fishes with habit alimentary piscivorous that they occupy the top of the trophic chain exercising a fundamental paper in the communities' structuring. This study had for objectives to analyze the feeding of the fish-dog, Acestrorhynchus pantaneiro in three rivers of Rio Grande do Sul, verifying which prey of larger preference and analyzing the relationship of the size of the prey x predator, and for Rio Vacacaí and Rio dos Sinos the group is considered allochthonous for the system. It was analyzed 380 examplaries captured bimonthly among the years of 2010 and 2011 for Rio Jaguari, which presented the index of vacuity of 0,74. In the rivers Vacacaí end of the Sinos 225 examplaries were analyzed, being 107 to Rio Vacacaí, captured in five points in the four seasons, presenting an index of vacuity of 0,62 and 118 examplaries captured to Rio dos Sinos in the summer and autumn of 2011, presenting result of IV of 0,41. In Rio Jaguari, differences were not verified between atmosphere lentic and lotic, regarding the capture, the bimonth with higher temperatures presented larger number of captured examplaries, and the studied species presented larger alimentary activity at dusk and at night to Rio Jaguari and at night for in the rivers Vacacaí end oh the Sinos. Through the analysis of the size of the prey x predator it could be verified for the three rivers studied that prey larger they are ingested by predators also larger. The diet of the species came fish-eating essentially feeding preferentially of small characins feeds. Studies of the alimentary behavior of species fish-eating are necessary, overcoat of species allochthonous, seeking to understand the relationships of those species as predators of chain top in aquatic atmospheres, controlling the feeds populations.